Flourishing at work across job sectors: The influence of big five personality traits - Sangadji, Khairul Mujahid; Choirunnisa, Zuyyinna; Masturah, Alifah Nabilah (Jurnal Ilmiah Psikologi Terapan, 2026)
A flourishing employee tends to have confidence in establishing broad and fulfilling social relationships. This capability is called flourishing, which is essential in the professional world. Several factors influence an individual’s capacity to flourish, including personality traits and the work environment. The primary objective of this study is to examine differences in flourishing across various work environments while controlling for the Big Five personality traits. This research adopts a quantitative comparative approach. The total number of participants in this study was 363 respondents, comprising 102 employees from State-Owned Enterprises, 113 employees from private companies, and 148 Civil Servants. The sampling technique used is accidental sampling. The study utilizes the Ten-Item Personality Inventory (TIPI) and the Flourishing Scale (FS) as measurement instruments. Data analysis is conducted using Analysis of Covariance (ANCOVA). The findings reveal that civil servants exhibit the highest level of flourishing compared to employees in SOEs and private companies when controlling for the Big Five personality traits. Furthermore, the results indicate that only the personality traits of extraversion and agreeableness significantly impact flourishing, whereas conscientiousness, emotional stability, and openness to experience do not exert a significant influence. Consequently, a work environment that ensures career stability is crucial in enhancing employees’ flourishing, regardless of their personality traits.